2020
DOI: 10.1074/mcp.ra119.001817
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Proteomics Identifies ERbeta Association with Chromatin Repressive Complexes to Inhibit Cholesterol Biosynthesis and Exert An Oncosuppressive Role in Triple-negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is characterized by poor response to therapy and low overall patient survival. Recently, Estrogen Receptor beta (ERβ) has been found to be expressed in a fraction of TNBCs where, because of its oncosuppressive actions on the genome, it represents a potential therapeutic target, provided a better understanding of its actions in these tumors becomes available. To this end, the cell lines Hs 578T, MDA-MB-468 and HCC1806, representing the claudin-low, basal-like 1 and 2 TNBC mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 77 publications
6
44
0
Order By: Relevance
“…In any case, full-length receptor expression was reported in a small fraction (15-20%) of TNBC patients, where its presence was correlated with better survival [13] and response to tamoxifen therapy [13], suggesting its possible use as both a prognostic marker and therapeutic target [14]. In accordance with this data, in our previous study [15] we demonstrated the oncosuppressive role of the full-length ERβ in three TNBC cell lines belonging to different TNBC subtypes.…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…In any case, full-length receptor expression was reported in a small fraction (15-20%) of TNBC patients, where its presence was correlated with better survival [13] and response to tamoxifen therapy [13], suggesting its possible use as both a prognostic marker and therapeutic target [14]. In accordance with this data, in our previous study [15] we demonstrated the oncosuppressive role of the full-length ERβ in three TNBC cell lines belonging to different TNBC subtypes.…”
Section: Introductionsupporting
confidence: 84%
“…Triple-negative breast cancer cell lines HCC1806 (CRL-2335), MDA-MB-468 (HTB-132), and Hs 578T (HTB-126) were purchased from the American Type Culture Collection (ATCC, Manassas, VA, USA) and maintained in culture as previously described [15]. Lentiviral particles containing viral RNA genome encoding for Tet-On Advanced and Inducible 3xFlag-ERβ were produced using Lenti-X Tet-On Advanced Inducible Expression System components (Takara-Clontech Europe, Göteborg, Sweden) according to the manufacturer's instructions.…”
Section: Tnbc Cell Line Maintenance and Erβ Clone Generationmentioning
confidence: 99%
See 3 more Smart Citations